2022
DOI: 10.1111/imb.12821
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA_XR209691.3 could promote Bombyx mori nucleopolyhedrovirus replication by interacting with BmHSP70

Abstract: Long non-coding RNAs (lncRNAs), a class of transcripts exceeding 200 nucleotides and lacking protein coding potential, have been proven to play important roles in viral infection and host immunity. Bombyx mori nucleopolyhedrovirus (BmNPV) is an important pathogen, which causes the silkworm disease and leads to a huge challenge to the sericultural industry. At present, research on the roles of insect lncRNAs in host-virus interaction are relatively few. In this study, we explored the function of lincR-NA_XR2096… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A. viridicyanea serves as a good material for investigating the adaptive evolution between insects and host plants. However, there have been few studies on the innate immunity of A. viridicyanea due to the lack of an adaptive immune system, which mainly depends on nonspecific immune responses, such as the activation of immune signaling pathways and production of antimicrobial peptides ( Lin et al, 2022 ; Wei et al, 2022 ). LncRNAs, incapable of translation into proteins, are significant regulators that regulate gene expression and are involved in various physiological and immunological functions at the transcriptional and posttranscriptional levels, such as the lncRNA-miRNA-mRNA axis based on the competitive endogenous RNA hypothesis ( Zhang et al, 2020 ; Lin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A. viridicyanea serves as a good material for investigating the adaptive evolution between insects and host plants. However, there have been few studies on the innate immunity of A. viridicyanea due to the lack of an adaptive immune system, which mainly depends on nonspecific immune responses, such as the activation of immune signaling pathways and production of antimicrobial peptides ( Lin et al, 2022 ; Wei et al, 2022 ). LncRNAs, incapable of translation into proteins, are significant regulators that regulate gene expression and are involved in various physiological and immunological functions at the transcriptional and posttranscriptional levels, such as the lncRNA-miRNA-mRNA axis based on the competitive endogenous RNA hypothesis ( Zhang et al, 2020 ; Lin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies on the innate immunity of A. viridicyanea due to the lack of an adaptive immune system, which mainly depends on nonspecific immune responses, such as the activation of immune signaling pathways and production of antimicrobial peptides ( Lin et al, 2022 ; Wei et al, 2022 ). LncRNAs, incapable of translation into proteins, are significant regulators that regulate gene expression and are involved in various physiological and immunological functions at the transcriptional and posttranscriptional levels, such as the lncRNA-miRNA-mRNA axis based on the competitive endogenous RNA hypothesis ( Zhang et al, 2020 ; Lin et al, 2022 ). In the last decade, accumulating evidence has confirmed the important roles of lncRNAs in the regulation of innate immunity in insects ( Valanne et al, 2019 ; Zhang et al, 2020 ; Zhang et al, 2021a ; Moure et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lncRNA IFITM4P acted as a positive regulator of innate antiviral immunity, involved in innate antiviral immunity, which resembled some interferon‐stimulated genes (ISGs) (Xiao et al, 2021). In our previous study, we found that cellular Lnc_209997 suppress Bombyx mori nucleopolyhedrovirus (BmNPV) replication by targeting miR‐275‐5p and LincRNA_XR209691.3 could promote BmNPV replication by interacting with BmHSP70 (S. Lin et al, 2022; Lin, Yin, et al, 2023). Besides, we also analyzed the alteration of lncRNA expression in silkworm infected with Bombyx mori cypovirus (BmCPV) for the first time and revealed the function of LINC20486 during BmCPV infection (data not shown) (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%